First reference on reproductive biology of Butis koilomatodon in Mekong Delta, Vietnam - Quang M. Dinh (BMC Zoology, 2021)
Abstract Background The key to fishery management is knowing the appropriate reproductive strategies of the targeted fish. For most gobiid species, the iteroparous pattern is dominant compared to semelparity. Albeit Butis koilomatodon plays an important role in the Mekong Delta’s food supply, its reproductive biological data have not been known. Hence, this study was conducted to provide new fundamental knowledge of reproductive traits of Butis koilomatodon in the Mekong Delta. Results A total of 1314 individuals (903 males and 411 females) were monthly collected by bottom gill nets from July 2019 to June 2020 at six sampling sites along estuarial and coastal regions, from Tra Vinh to Ca Mau provinces, southern of Vietnam. pH and salinity of these six sampling sites are 7.72–7.93 pH and 11.17–26.17‰, respectively. The pH varies with sites, but not seasons; whereas a reverse case is found in salinity. Different types of oocytes are found in histological specimens of ovaries prove that B. koilomatodon is a multi-spawner. The gonadosomatic index value, together with the monthly presence of mature ovaries reveal that this species spawns throughout the year. The length at first mature male Butis koilomatodon (5.1–8.6 cm) is higher than that of females (4.8–6.7 cm), except in Hoa Binh and Dong Hai. Batch fecundity (3085 to 32,087 eggs/female) increases with fish weight (1.48–12.30 g) and length (4.8–9.0 cm) due to high determination values (r 2  > 0.6). Conclusion Knowledge of reproductive traits gained from this study was a reference source for future studies and helped manage this species’ resources.